Ecology and development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Ecology and Development in the Third World' / Avijit Gupta, 1988 , 80pp, ISBN 0 415 00673 2, price UKL5.95. Routledge - 11 New Fetter Lane London EC4P 4EE - UK